2016
DOI: 10.26789/aeb.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation and characterization of symbiotic bacteria from the gut of Reticulitermes chinensis

Abstract: Cultivation and characterization of symbiotic bacteria from the gut of Reticulitermes chinensis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Two other bacteria ( Citrobacter and Ochrobacterium ) that were not very abundant in the guts of BSFL also promote BSF growth and development. Citrobacter is frequently detected and isolated from the guts of various insects, like termites, BSF, and the oriental fruit fly (Fang et al ., 2016; Guo et al ., 2017; Cai et al ., 2018). Previous studies have shown that Citrobacter promotes cellulose degradation (Fontes‐Perez et al ., 2015) and enhances the resistance of the oriental fruit fly to insecticides (Cheng et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Two other bacteria ( Citrobacter and Ochrobacterium ) that were not very abundant in the guts of BSFL also promote BSF growth and development. Citrobacter is frequently detected and isolated from the guts of various insects, like termites, BSF, and the oriental fruit fly (Fang et al ., 2016; Guo et al ., 2017; Cai et al ., 2018). Previous studies have shown that Citrobacter promotes cellulose degradation (Fontes‐Perez et al ., 2015) and enhances the resistance of the oriental fruit fly to insecticides (Cheng et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The PCR mixture and amplification procedure were as described by Fang et al . (2016). Strains were classified using amplified ribosomal DNA restriction analyses.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent studies investigating the reservoir of Y. regensburgei have increased the understanding of its animal reservoir to include insects such as southern green stink bug (Nezara viridula), brown stink bug (Euschistus heros), giant spiny stick insect (Eurycantha calcarata), termites (Reticulitermes chinensi), boxelder bug (Boisea trivittata). Addditionally, Y. regensburgei has also been isolated from soil samples in China, thus greatly expanding its known natural reservoir [15,[18][19][20][21][22][23]. However, veterinary infections produced by this bacterium were not reported until recently.…”
Section: An Emerging Pathogen In the Animal Worldmentioning
confidence: 99%